Analisis Hukum Partisipasi Masyarakat Dalam Proses Pembentukan Peraturan Perundang-Undangan - Izza Difanda Hanania (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
This research aims to analyze community participation in the process of forming laws and regulations and the obstacles that accompany it. Community participation in the process of forming laws and regulations is a concrete manifestation of the implementation of sovereignty which is in the hands of the people. Regulations regarding community participation are regulated in Article 96 of Law Number 13 of 2022 which is an amendment to Law Number 12 of 2011. This regulation accommodates community participation which can be provided by providing written and verbal input, both online and offline regarding each stage of formation. The research uses normative methods and a legislative and conceptual approach that examines related laws and regulations descriptively. The research results show that community participation can be channeled through listening meetings, outreach, work visits, and various other forms of discussions facilitated by the government. However, in implementing community participation, normatively there are still several obstacles or evaluations regarding regulations, namely (1) limitations in the meaning of "community" who can submit their opinions or input to the process of forming statutory regulations; (2) limited evaluation materials that can be used as a basis for the community in providing their aspirations or input because based on Article 96 paragraph (4), the only ones that are open to access to the public are academic texts and draft regulations; (3) participation activities can only be carried out based on the wishes of the legislators; (4) there is no time limit or at least a minimum number of times the activity will be held; and (5) lack of implementing regulations relating to the regulations in Article 96 paragraph (9) because regulations regarding public participation should be regulated in DPR Regulations, DPD Regulations and Presidential Regulations.